2020
DOI: 10.3390/ma13102380
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution, Mechanical Properties and Deformation Behavior of an Additively Manufactured Maraging Steel

Abstract: In this work, the microstructure and mechanical properties of an additively manufactured X3NiCoMoTi18-9-5 maraging steel were determined. Optical and electron microscopies revealed the formation of melt pool boundaries and epitaxial grain growth with cellular dendritic structures after the laser powder bed fusion (LPBF) process. The cooling rate is estimated to be around 106 °C/s during solidification, which eliminates the nucleation of any precipitates. However, it allows the formation of austenite with a vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…The higher hardness of the 18Ni-300 maraging steel manufactured additively has been attributed to the fine microstructure that results from the rapid cooling conditions during LPBF processing [26]. Previously, Bai et al [11] reported an average microhardness value of 381 HV 0.2 , and Chada et al [59] reported 35 ± 1 HRC for as-printed 18Ni-300 maraging steel manufactured with stand-alone LPBF technologies, which support the present findings for the 18Ni-300 maraging steel produced by hybrid manufacturing with the Matsuura LUMEX Avance-25 technology reasonably well. reported as 30-32 HRC [2].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher hardness of the 18Ni-300 maraging steel manufactured additively has been attributed to the fine microstructure that results from the rapid cooling conditions during LPBF processing [26]. Previously, Bai et al [11] reported an average microhardness value of 381 HV 0.2 , and Chada et al [59] reported 35 ± 1 HRC for as-printed 18Ni-300 maraging steel manufactured with stand-alone LPBF technologies, which support the present findings for the 18Ni-300 maraging steel produced by hybrid manufacturing with the Matsuura LUMEX Avance-25 technology reasonably well. reported as 30-32 HRC [2].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The higher hardness of the 18Ni-300 maraging steel manufactured additively has been attributed to the fine microstructure that results from the rapid cooling conditions during LPBF processing [26]. Previously, Bai et al [11] reported an average microhardness value of 381 HV0.2, and Chada et al [59] reported 35 ± 1 HRC for asprinted 18Ni-300 maraging steel manufactured with stand-alone LPBF technologies, which support the present findings for the 18Ni-300 maraging steel produced by hybrid manufacturing with the Matsuura LUMEX Avance-25 technology reasonably well. Next, the mechanical response of the as-printed 18Ni-300 maraging steel was evaluated by uniaxial tensile testing to obtain the engineering strain-stress curves, as shown in Figure 9, and to determine the average values for the YS, UTS, EL, and E, as tabulated in Table 6 for the coupons built at the four different power levels.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…In all, the composite-forming process as a new technology where the large ring parts are formed by hot rolling, based on the as-cast billet, keeps gaining attention. The shape-controlling technology of the casting-rolling forming process tends to be perfect [ 30 , 58 ], while the performance-controlling technology is still in a technical bottleneck [ 25 , 26 ]. From a research perspective, except for a heat treatment investigation in the casting-rolling forming process, the grain refinement mechanism during plastic deformation and the performance-controlling of X6CrNiMoVNb11-2 steel need to be investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…The hot deformation parameters of ring-rolling processing have been optimized to investigate the deformation rules of disk pieces [ 21 ]. However, for this kind of Fe-Cr-Ni-Mo martensitic stainless steel, research on the heat-treatment process of X6CrNiMoVNb11-2 steel only focuses on conventional annealing, quenching, tempering and nitriding treatments [ 21 , 22 , 23 , 24 , 25 , 26 ], the influencing rule of the cooling medium on yield strength, tensile strength, elongation and impact toughness during quenching and tempering has not yet been identified. Hence, the current research on mechanical properties under different cooling conditions by means of a mechanical property test is very limited [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organizations that efficiently collect and use data are doing better and better on the market, and in some industries it is essential for market success. Establishing quantitative relationships between phenomena allows you to draw more accurate conclusions and, based on them, make decisions with fewer errors in the areas of quality control, monitoring error rates, improving operational efficiency, reducing costs, analyzing product lines, increasing revenue, evaluating sales, analyzing and reporting compliance, and evaluating projects to identify new opportunities or hidden problems [ 10 ].…”
Section: Introductionmentioning
confidence: 99%